Does a Higher Prevalence for Primary Diagnosis of Crohn's Disease Involve the Upper Gastrointestinal Tract?. Issue 9 (September 2016) - Cai, Lin; Zhang, Tao; Wang, Chunhui
Abstract : Article first published online 9 August 2016.